Syria's sectarian quandary: Without solving Sunni dispossession, the Geneva talks skirt around the conflict - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2017)
A U.S. missile strike against the Assad regime in response to a suspected chemical weapons attack may have lessened a fear of Russia among countries that nominally back the Syrian opposition. Renewed U.S. diplomatic engagement in Syria could relieve pressure on the opposition to accept a settlement at the Geneva talks, which would be little more than a facelift of the Alawite-dominated regime. The international environment has lacked the balance to redress the disenfranchisement of Syria's majority Sunni population - a root cause of the war. European states hope to employ their reconstruction funding capacity. But stabilization remains far-fetched without a political transition and an inclusive system that can end the Assad clan's monopoly on power. (SWP Comments)
Keywords: 320